Association of the Neuropeptide Y LEU7PRO rs16139 and NEUREXIN 3 rs760288 Polymorphisms with Alcohol Dependence. Issue 1 (1st March 2016) - Sengul, Cem; Erdal, Mehmet Emin; Sengul, Ceyhan Balci; Ay, Ozlem Izci; Buber, Ahmet; Alacam, Huseyin; Ay, Mustafa Ertan; Herken, Hasan
ABSTRACT: Objective : Alcoholism is associated with genetic variants of genes related to alcohol metabolizing enzymes, dopaminergic, gamma-aminobutyric acidergic, glutamatergic, opioid, cholinergic, and serotonergic systems. Neurpeptide Y system and Neurexins were shown to be associated with alcohol dependence. Recent studies identified new genetic polymorphisms related to endogenous cannabinoid system, neuropetide Y and neurexin. In the present study, we aimed to investigate the association of Neurpeptide Y LEU7PRO rs16139 and neurexin 3 gene rs760288 polymorphisms with alcohol dependence in patients with alcohol dependence and healthy control subjects. Methods : 123 patients who were diagnosed with alcohol dependence according to the DSM-IV criteria and 159 healthy volunteers were included in the study. Blood samples were used to investigate polymorphisms. The genotyping of the neurexin 3 gene rs760288 and the neuropetide Y gene Leu7Pro rs16139 polymorphisms was performed using TaqMan SNP Genotyping Assays Real-Time PCR System. Results : Of the 2 genetic polymorphisms investigated in the present study, we detected association between and neurexin 3 gene rs760288 polymorphisms with alcohol dependence. Conclusions : Neurexin gene polymorphisms might be an important factor in development of alcohol addiction.